DAMPAK FILM TERHADAP KEHIDUPAN PSIKOLOGIS, SOSIAL, DAN KULTURAL MANUSIA DI ERA MEDIA AUDIOVISUAL - Yehezkiel Artseno (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Film is not merely a form of entertainment but a powerful mass communication medium capable of shaping emotions, perceptions, values, identities, and social behavior. This study aims to analyze comprehensively the psychological, social, and cultural impacts of film on human life in the contemporary audiovisual era. Using a qualitative descriptive approach through an extensive literature review, this research examines how films influence emotional responses, identity construction, moral reasoning, social attitudes, and behavioral patterns. The findings reveal that films function as instruments of emotional catharsis, social learning, cultural transmission, and ideological reinforcement. However, films also pose risks such as normalization of violence, reinforcement of stereotypes, unrealistic life expectations, and passive audience consumption. This study emphasizes the urgency of media literacy and critical viewing skills to ensure that film consumption contributes positively to individual well-being and social development.